PENGARUH DUKUNGAN SOSIAL ORANG TUA, MINAT BELAJAR DAN PROKRASTINASI AKADEMIK TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN EKONOMI PADA SMA NEGERI AKREDITASI A DI KOTA PADANG - Chientya Annisa Rahman (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2019)
This research aims to identify and analysis: (1) The effect of social support for student academic procrastination, (2) The effect of interest in student academic procrastination, (3)The effect of social support of parents on student learning outcomes on economic subjects, (4) The effect of academic procrastination on student learning outcomes on economic subjects, (5) Effect of interest in learning on learning outcomes of students in economic subjects. The results of this study shows that: (1) There is a significant and negative relationship between social support of parents on academic procrastination, (2) There is a significant and negative relationship between interest in student academic procrastination, (3) There is a significant and negative relationship between social support of parents on student learning outcomes,(4) There is a significant and negative relationship between academic procrastination on student learning outcomes, (5) There is a significant and negative relationship between interest in learning on learning outcomes of students. Based on the result of research, it is advisable for parents to be able to give attention to the children in learning. It is advisable for students to be able to set the time in task. Repeat learning and increase knoledge of subjects that achieved with good results. And for futher research is expected to examine other foctors that affect academic procrastination.